Analysis of Problems in the Implementation of Science Practical at Junior High School, Gorontalo Regency - Tirtawaty Abdjul; Nur Azizah Dj. Junus; Nyoman Sriastuti; Risna H. Panyo (Jurnal Pijar MIPA, 2026)
Science practicums are an essential component of the Independent Curriculum to develop students’ science process skills, yet their implementation at the junior high school level still faces various obstacles. This study aims to analyze problems in the implementation of science practicums at SMPN 1 Telaga Biru, Gorontalo Regency. A qualitative approach was used, with data collected through observation, semi-structured interviews with four science teachers, and a literature review. Data were analyzed using thematic analysis involving data reduction, coding, categorization, and conclusion drawing. The results reveal three interrelated problems: (1) limited facilities and infrastructure, such as damaged tools and insufficient practicum materials; (2) limited instructional time; and (3) low teacher competency in operating practicum equipment due to minimal training. These constraints reduce the effectiveness of practicum-based learning and hinder the development of students’ science process skills. This study concludes that improving practicum implementation requires integrated efforts in enhancing facilities, time management, and teacher competency. The findings provide a comprehensive basis for improving educational policy and practice, particularly through better resource allocation, flexible scheduling, and continuous professional development for teachers.